Management of Non-A Non-B Aortic Dissection: A Narrative Review - Joseph Kletzer; Stoyan Kondov; Aleksandar Dimov; Victoria Werdecker; Martin Czerny; Maximilian Kreibich; Tim Berger (Journal of Cardiovascular Development and Disease)
Non-A non-B aortic dissection remains a complex and controversial topic in cardiovascular management, eliciting varied approaches among cardiologists and surgeons. Due to the limited evidence surrounding this condition, existing guidelines are limited in the complexity of their recommendations. While most patients are initially managed medically, invasive treatment becomes necessary in a large proportion of patients. When surgery is considered, the most utilized techniques include the frozen elephant trunk procedure and endovascular repair strategies targeting the arch and descending thoracic aorta. This narrative review aims to synthesize current knowledge and clinical experiences, highlighting the challenges and evolving practices related to non-A non-B dissection management.